Extended operation range of photovoltaic inverters by current waveform shaping - Bruske, Sebastian; De Carne, Giovanni; Buticchi, Giampaolo; Liserre, Marco; Zhang, He (Institute of Electrical and Electronics Engineers Inc., 2020)
The grid connection of photovoltaic voltage source inverters depends on the dc-link voltage level that can be supplied by the maximum power tracking of the photovoltaic system. The inverter disconnects from the grid, if the minimum required dclink voltage level is violated, which leads to unwanted energy curtailments implying losses to the system owner. This paper proposes to apply current waveform shaping to the inverter current in order to reduce the peak value of the voltage waveform at the point of common coupling by which the minimum required dc-link voltage level for power injection is reduced. This extended operation range of photovoltaic inverters is achieved through third harmonic current injection and can be applied to single-phase and three-phase, four-wire inverters without additional converter stages. A control structure for harmonic current injection and harmonic phase determination is presented and validated by simulations and the analysis is verified by experiments.